2007
DOI: 10.1002/cncr.22913
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid carcinomas with a variable insular component

Abstract: BACKGROUND. An insular growth pattern may be observed focally both in papillary and follicular thyroid carcinoma. The aim of the current study was to determine whether a greater extension of the insular component (IC) influences different clinical and histologic features at diagnosis, and a different tumor aggressiveness in terms of frequency in the occurrence of metastases as well as survival. METHODS. Thirty‐three patients with histopathologic findings consistent with IC were included in the study. IC was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
(31 reference statements)
3
10
0
Order By: Relevance
“…This result is noteworthy considering the higher rate of EBRT use in patients with distant metastasis compared with those assigned a lower disease stage. Although RAI uptake in ITC has been reported, there are conflicting data regarding the impact of radiation‐based therapy on the outcomes of patients with ITC 14, 19, 21, 22, 24, 38. Similar to our results, Rufini et al22 demonstrated improved outcomes for patients with ITC who received RAI treatment.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This result is noteworthy considering the higher rate of EBRT use in patients with distant metastasis compared with those assigned a lower disease stage. Although RAI uptake in ITC has been reported, there are conflicting data regarding the impact of radiation‐based therapy on the outcomes of patients with ITC 14, 19, 21, 22, 24, 38. Similar to our results, Rufini et al22 demonstrated improved outcomes for patients with ITC who received RAI treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Although RAI uptake in ITC has been reported, there are conflicting data regarding the impact of radiation‐based therapy on the outcomes of patients with ITC 14, 19, 21, 22, 24, 38. Similar to our results, Rufini et al22 demonstrated improved outcomes for patients with ITC who received RAI treatment. In contrast, Pellegriti et al21 observed a clinical benefit from RAI in only 1 patient despite good RAI uptake in all 11 patients who had ITC with metastatic disease in their study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Several papers agree with the evidence that CXCR4 expression is under the control of the RET/PTC-RAS-BRAF-ERK pathway in WDC (mainly PTCs), mediating an upregulation through BRAF activation and ending in inducing aggressive lymph node involvement. 34 Otherwise, a more typical vascular metastatic process in the PDs should be the final result of both CXCR4-SDF-1a downregulation and BRAF wild type. 16,21,22 The role of the molecular genotype has been largely studied in "pure" PD cancers, demonstrating that RAS, BRAF, RET/PTC or PAX8/PPRg show discordant results merely linked with worse prognosis in cases with high K-RAS expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the WHO book, the "majority" of such growth patterns is mentioned as a requirement, although controversial conclusions have been reached by different groups that applied different thresholds, and some reports demonstrated that even minor STI components may affect prognosis [6,10,18,20]. Recently, a significantly different prognosis was observed using a 50% cutoff of STI areas [21]. In our experience, however, the vast majority of cases of PD thyroid carcinomas that meet the diagnostic criteria listed above display STI architecture as the predominant growth pattern, whereas cases with focal STI growth usually do not present high grade features nor follow an aggressive behavior.…”
Section: Extent Of Sti Patterns To Be Recognizedmentioning
confidence: 97%